Sharing and neoliberal discourse: The economic function of sharing in the digital on-demand economy. (December 2016) - Cockayne, Daniel G.
Abstract: In this paper I offer a critical analysis of 'sharing' as a discursive formation in the emerging on-demand economy or, as its more commonly known, 'sharing' economy. The set of firms and digital platforms that constitute the on-demand economy evade precise definition, though in popular commentary include Uber, Lyft, Airbnb, Taskrabbit, Couchsurfing, and Yelp, among others. I argue that sharing is a discursive formation that is produced through neoliberal economic practices and contributes to their constitution and performance, connoting the embeddedness and inter-determination of the economic with the social. I analyze interview material with software developers and others working for on-demand economy firms in San Francisco to underscore how the sharing discourse is produced, and to examine the possible relationship between the sharing discourse and working practices in the on-demand economy. I explore how sharing, though a fragile and contested discourse, has been used by some proponents of the on-demand economy in an attempt to justify and normalize flexible and precarious work through an ambiguous association between capitalist exchange and altruistic social values. This ambiguity is productive insofar as sharing has become associated variously with transactional platforms, digital peer review via surveillant and punitive ratings systems, and algorithmically mediated, precarious, and 'entrepreneurial' contract work, while retaining affective associations with community, inclusion, and participation.